Two Ontologies of Power: A Comparison of Santayana and Tillich - Comstock, W. Richard (Harvard theological review, 1967)
The positions of George Santayana and Paul Tillich disclose remarkable strands of congruent concern and approach. In spite of obvious differences in temperament and philosophical heritage, both thinkers see their philosophies as the culmination of traditional perspectives in Western thought and also as modern criticisms of them. Neither thinker is interested in a radical originality of thought severed from its roots in the past. Both rather want to formulate a general philosophy of culture that is eclectic in the best sense of that abused word.Working independently of each other, both finally focus their attention on a similar concern that they see operating in the tradition and which is considered by them to have a continuing importance in the present. This is the problem of power and the appropriate human response to its manifestations. The intriguing features of agreement and disagreement in this common exploration are examined in the present essay.